A short history of Thomism - Cessario, Romanus (Catholic University of America Press, 2005)
"Since the first followers of Saint Thomas Aquinas took up the task of explaining and defending his writings, Thomists have influenced deeply the Western intellectual tradition. Together they form a school called Thomism that can claim an uninterrupted history since the end of the thirteenth century. Using carefully selected resources, Romanus Cessario has composed a short account of the history of the Thomist tradition as it manifests itself through the more than seven hundred years that have elapsed since the death of Saint Thomas. A Short History of Thomism, originally published in French as Le Thomisme et les Thomistes, supplies a need that has not been met in over a century, and is the first such comprehensive account written in English."--Jacket.